Knowledge sharing behaviour among students in learning environments: a review of literature - Ghadirian, Hajar; Mohd Ayub, Ahmad Fauzi; Silong, Abu Daud; Abu Bakar, Kamariah; Hossein Zadeh, Ali Mohammad (Canadian Center of Science and Education, 2014)
Knowledge sharing is critical element for intellectual discourses. However, knowledge sharing is a demanding task that takes time and effort and requires students to be persistent and willing to interact with each other. Recognizing factors that impact knowledge sharing in learning communities is critical. This paper reviews the current literature on knowledge-sharing among students in learning environments, discusses possible factors affecting knowledge sharing behavior among students, and provides future research opportunities. A search of the literature was performed across the ERIC and Academic Search Premier. Empirical studies were included for review if they specifically examined the impact of possible sets of factors on knowledge sharing in learning environments. Key features of articles were classified at the four areas of emphasis: theoretical framework, context of the study, predictive variables, and conceptualization of knowledge sharing and its dimensions. This classification provides a means for educators, instructional designers and curriculums developers to identify key factors involved in successful knowledge sharing process. However, given the limited number of studies currently available, further research is required to establish clear conclusion and recommendation.